ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. SUMMARECON AGUNG Tbk (SMRA) VS ALAM SUTERA REALTY Tbk (ASRI) PERIODE TAHUN 2020 - 2021 - Erwin Hanggoro Agung Nugroho; Sri Hermuningsih (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to analyze the financial performance of PT Summarecon Agung Tbk (SMRA) and PT Alam Sutera Realty Tbk (ASRI) for 2020 and 2021. In conducting the analysis, data from the financial statements of SMRA and ASRI for 2020 and 2021 will be collected and calculated by using financial ratios commonly used in performance analysis, such as profitability ratios, liquidity ratios, and solvency ratios. In addition, the debt-to-equity ratio and interest coverage ratio. The performance comparison of SMRA vs ASRI in 2020 and 2021 shows quite interesting results. SMRA is one of the largest property companies in Indonesia, while ASRI is a property company that focuses more on developing areas that are in the premium category. The comparison between the two companies shows that ASRI's performance is more stable compared to SMRA, which was burned by unfavorable market conditions in 2020. However, SMRA managed to show significant improvement in 2021 and is likely to continue to increase along with a better economic recovery.